Grid Current Feedback Active Damping Control Based on Disturbance Observer for Battery Energy Storage Power Conversion System with LCL Filter - Ning Gao; Xin Lin; Weimin Wu; Frede Blaabjerg (Energies, 2021)
Adopting the battery energy storage system is an effective way to compensate the continuously growing fluctuating power generated by renewable sources. The power conversion system is considered as one of the core equipment used for interfacing battery packs to the grid in a battery energy storage system. This paper aims to apply an improved active damping control to a grid-tied power conversion system with LCL filter to attenuate its inherent resonance characteristics. The anti-interference ability is enhanced by estimating the second-order derivation of grid-injected current based on a modified disturbance observer. Meanwhile, the negative effects of parameter mismatch are equivalent to unmeasurable disturbances, which are possible to be compensated by subtracting the estimated values from the modulated voltage references. Moreover, the design method and robustness issue of the disturbance observer are discussed in detail. The presented control algorithm is implemented based on Simulink and dSpace. Detailed simulation results are provided, which can verify the feasibility and correctness of control strategy. Furthermore, an experimental prototype rated at 2.3 kW/110 V is constructed. The experimental results confirm that the presented control method is effective to be applied in the power conversion system (PCS).